Maternal and Perinatal Complications of Vascular Pathologies Associated with Pregnancy: Frequency and Associated Factors in a Third Level Maternity in Benin - TOGNIFODE, Véronique; ABOUBAKAR, MOUFILATOU; OGOUDJOBI, OGOURINDÉ MATHIEU; TSHABU TSHINGUTA ÉPSE AGUEMON, CHRISTIANE (My University, 2022)
Abstract: Background and aims: Vascular pathologies (hypertensive disorders and diabetes) associated with pregnancy are important public health problem in Benin because of their frequencies and their complications. This study aims to analyze maternal and perinatal complications of vascular pathologies associated with pregnancy. Methods: This analytical cross-sectional study used retrospective data collected over a three-year period. All mothers who presented a vascular pathology and their newborns during the study period at the Clinique Universitaire de Gynécologie obstétrique (CUGO) of Centre National Hospitalier Universitaire Hubert Koutoukou Maga (CNHU-HKM) of Cotonou were included. Maternal complications associated neurological, hematological, cardio-pulmonary and renal complications whereas perinatal complications included intrauterine growth restriction, fetal asphyxia, prematurity, neonatal resuscitation, low birthweight and perinatal death. Factors associated to the complications were identified by using chi-square test and a multivariate binary logistic regression model. Analyzes were performed with SAS software version 9.4. Results: The frequency of vascular pathologies associated with pregnancy was 14.95%. Diabetes was associated in 4.57%. Their evolutions were marked by the occurrence of numerous maternal complications dominated by retroplacental hematoma (12.08%), eclampsia (08.37%) which passed through signs of eclampsism (21.07%); and hellp syndrome. Perinatal complications were dominated by prematurity (43.07%), low birthweight (29.12%), fetal asphyxia (12.32%) and perinatal death (18.59%). These complications were associated with the precocity of the diagnosis, admission mode and the importance of proteinuria. Conclusion: Maternal and perinatal complications of vascular pathologies associated with pregnancy are frequent in current obstetric practice. It is therefore urgent to implement health promotion interventions targeting the factors associated with them in order to reverse the trends.
Keywords: Complications; Maternal; Perinatal; Vascular Pathologies; Pregnancy